MUC16 C terminal-induced secretion of tumor-derived IL-6 contributes to tumor-associated Treg enrichment in pancreatic cancer. (1st April 2018) - Fan, Kun; Yang, Chao; Fan, Zhiyao; Huang, Qiuyi; Zhang, Yiyin; Cheng, He; Jin, Kaizhou; Lu, Yu; Wang, Zhengshi; Luo, Guopei; Yu, Xianjun; Liu, Chen
Abstract: Pancreatic cancer is the most lethal tumor. CA125 (gene symbol MUC16) is an important serum marker for pancreatic cancer diagnosis and treatment. High serum CA125 is related to metabolic tumor burden and poor prognosis. The circulating Treg subset is another independent prognostic factor for pancreatic cancer. Our unpublished data indicated that the circulating Treg proportion might be related to the serum CA125 level. However, the potential relationship and underlying mechanism of MUC16 and Treg in pancreatic cancer tissues remain unclear. In this study, we found that pancreatic cancer tissues were positive for both MUC16 C terminal (MUC16c) and Foxp3 expression and that their expression was correlated. MUC16c released into the cytoplasm via EGF induction significantly increased IL-6 expression and secretion. The PI3K/AKT pathway may participate in the regulation of IL-6 expression and secretion. By treating CD4 + T cells with IL-6 or co-culturing the cells with pancreatic cancer cells, tumor-derived IL-6 was identified to promote Foxp3 expression and Treg differentiation, which was significantly inhibited by the JAK2 inhibitor AG-490. In sum, our study demonstrated that the relationship between the MUC16c level and Foxp3 expression in the local tumor environment was consistent with that of the serum CA125 level and circulating Treg proportion in the systemic environment. MUC16c promoted Foxp3 expression and tumor-associated Treg enrichment in tumor tissues through tumor-secreted IL-6 activation of the JAK2/STAT3 pathway. These findings may provide deeper insight into potential pancreatic cancer therapy approaches. Highlights: MUC16c and Treg were significantly correlated, and both of them were novel prognostic indicators for pancreatic cancer. IL-6 mediated the "cross-talk" between tumor cells and stromal immune cells, and contributed Treg enrichment. The potential mechanism between MUC16c and Treg indicated an "cross-talk" in tumor cells and local immune microenvironment.